THE ANTI-FUNGAL PROPERTIES OF AQUEOUS EXTRACTS FROM PSOROLEA CORYLIFOLIA LINN. SEEDS IN CONTROLLING GRAIN SMUT AND SEED QUALITY ENHANCEMENT OF SORGHUM - C. MATHAD, RAKESH; N. M. SHAKUNTALA; S. N. VASUDEVAN; NAIK , M. NAGARAJ; S. B. PATIL (The Bioscan, 2013)
There are numerous cultivated medicinal plants like Babchi (Psorolea corylifolia Linn. used in folkore medicines for treatment of many human diseases. In an experiment at UAS, Raichur, the aqueous extract of seeds of this plant was treated with sorghum seeds infected with grain smut to know the effect on disease control and seed quality enhancement. The babchi oil treated along with a clear and inert polymer at 5-6 mL/kg seeds almost reduced the infection level and disease severity index to 50%. The seeds treated with 8 mL/kg seeds produced lowest infection level (20.40%) and disease severity index (10.2). Also this seed treatment recorded highest seed quality enhancement like germination (84%), seedling vigour index (1688), seedling dry weight (0.32g), relative dry weight (1.9g) and 100 seed weight (5.2g).